Youth Work : An Institutional Ethnography of Youth Homelessness - Nichols, Naomi, 1978- (Book collections on Project MUSE., 2014)
Combining institutional ethnography and community-based research, Youth Work is a sophisticated examination of the troubling experiences of young people living outside the care of parents or guardians, as well as of the difficulties of the frontline workers who take responsibility for assisting them. Drawing from more than a year of on-site research at an Ontario youth emergency shelter, Naomi Nichols exposes the complicated institutional practices that govern both the lives of young people living in shelters and the workers who try to help them.